Penanganan Perdagangan Narkoba di Indonesia oleh UNODC Tahun 2017-2020 - Rolando, Eric; Hapsari, Renitha Dwi (Department of International Relations, Hasanuddin University, 2024)
The high population in Indonesia makes it a potential market for transnational criminal groups to use Indonesia as a transit and distribution hub for drug trafficking. Given the current issues, UNODC, as an international organization specializing in addressing transnational crimes, assists Indonesia in dealing with the issue of drug trafficking. This research aims to understand the role of UNODC in tackling the problem of drug trafficking in Indonesia. The study employed a descriptive research design, and research data is obtained through library research by searching for data sources through available literature. This research is based on the theory of international organization roles according to Kelly Kate Pease, which explains that international organizations have several roles, including being problem solvers and capacity builders. The research findings show that UNODC plays a role in addressing the issue of drug trafficking in Indonesia through its role as a problem solver by formulating the Indonesia country program and alternative development programs. Meanwhile, through its role as a capacity builder, UNODC enhances the capacity of government officials, staff, and the community by treatnet family programme. Jumlah penduduk yang tinggi di Indonesia menjadikannya pasar potensial bagi kelompok kejahatan lintas negara untuk menggunakan Indonesia sebagai pusat transit dan distribusi perdagangan narkoba. Mengingat masalah saat ini, UNODC, sebagai organisasi internasional yang mengkhususkan diri dalam mengatasi kejahatan lintas negara, membantu Indonesia dalam menghadapi masalah perdagangan narkoba. Penelitian ini bertujuan untuk memahami peran UNODC dalam mengatasi masalah perdagangan narkoba di Indonesia. Studi ini menggunakan desain penelitian deskriptif, dan data penelitian diperoleh melalui penelitian perpustakaan dengan mencari sumber data melalui literatur yang tersedia. Penelitian ini didasarkan pada teori peran organisasi internasional menurut Kelly Kate Pease, yang menjelaskan bahwa organisasi internasional memiliki beberapa peran, termasuk sebagai penyelesaian masalah (problem solver) dan pembangun kapasitas (capacity builder). Temuan penelitian menunjukkan bahwa UNODC berperan dalam mengatasi masalah perdagangan narkoba di Indonesia melalui peran sebagai penyelesaian masalah dengan merumuskan program negara Indonesia dan program pengembangan alternatif. Sementara itu, melalui perannya sebagai pembangun kapasitas, UNODC meningkatkan kapasitas pejabat pemerintah, staf, dan masyarakat melalui program keluarga treatnet.